Obtaining real-world evidence: the Salford Lung Study. Issue 12 (6th March 2014) - New, John P; Bakerly, Nawar Diar; Leather, David; Woodcock, Ashley
Abstract : We need to assess clinical treatments in real-life settings outside of randomised controlled trials (RCTs). Pragmatic RCT (pRCT) data can supplement RCTs by providing effectiveness information to support healthcare decisions. Electronic health records can facilitate concurrent safety monitoring and data collection without direct patient contact for large randomised study populations in pRCTs. The Salford Lung Study is the world's first phase III pRCT in asthma and chronic obstructive pulmonary disease (COPD), which aims to randomise over 7000 patients. This paper describes the hurdles overcome and the enormous effort and resource required to establish this comparative effectiveness study of a prelicence intervention. GlaxoSmithKline protocol: HZC115151 Asthma study clinicaltrials.gov registration: NCT01706198 COPD study clinicaltrials.gov registration: NCT01551758